Redox mediators promote electrochemical oxidation of nitric oxide toward ambient nitrate synthesis. Issue 3 (9th January 2023) - Liang, Jie; Zhang, Longcheng; He, Xun; Wang, Yan; Luo, Yongsong; Zheng, Dongdong; Sun, Shengjun; Cai, Zhengwei; Zhang, Jing; Ma, Ke; Zheng, Yinyuan; Sun, Xuping; et al.
Abstract : Under ambient conditions, using low concentration NO (1%), ultrahigh nitrate formation rates in a two-electrode system can be achieved via the eCOR-NOOR. The structure changes of electrode materials under real reaction conditions are revealed. Abstract : Nitrate is an abundantly produced chemical with great importance in agriculture, military, and a variety of industries, notably for manufacturing fertilizers, but it is synthesized via the energy- and waste-intensive Haber–Bosch and Ostwald processes. Ambient nitrate synthesis by nitric oxide (NO) electrooxidation is an attractive technology but it represents a significant challenge in electrochemistry due to the ultralow solubility of NO. Herein, we report a facile approach to achieve truly effective, economic, and eco-friendly nitrate synthesis by expanding conversion sites from a limited electrode surface to the entire electrolyte, with the assistance of chlorine (electro) chemistry. Introduction of chlorine-cycle as a redox mediator dramatically boosts nitrate formation rates to 115.45 mg cm −2 h −1 (three-electrode system) and 790.1 mg cm −2 h −1 (two-electrode system) with a low NO concentration of 1%, both far exceeding those of state-of-the-art nitrogen electrooxidation, confirming the remarkable effectiveness of our strategy in producing nitrate homogeneously and electrochemically. Importantly, almost no side product nitrite is generated in this work. In addition, the structure changes of electrodes are investigated using (quasi)- in situ techniques.